The Role of Islamic religious law in developing the conceptualization of Intercultural Competence - Bychou, Omar (Journal of Humanities & Social Sciences, 2022)
This article aims to identify the role of Islamic religious law in improving the management of multiculturalism internationally. It develops the literature on the theoretical foundations of the concept of intercultural competence. In order to do this, it is necessary to examine the issue of cultural diversity within the competency approach and the origin of the differences between these models and their identities, which are critical to the relationship between ethical values and competencies. This illustrates the necessity of researching ways to develop intercultural competence. We have adopted the descriptive-analytical approach in reading and analyzing texts from the Holly Qur’an and scientific research related to the topic. It evaluates the framework of possible ways of investigating intercultural competence, including those possibilities which have not yet been completed. It is obvious to us that one must choose a conception of Islamic culture that takes account of civilizational resources that can manage unity and difference. In this way, we will show that Islamic culture specifically law represents a rich resource of knowledge concerning the moral and ethical dimensions of communication between cultures. In the light of the results of this study, we have a number of recommendations among which is the spread of consciousness among the institutions promoting multiculturalism and for researchers working on the theory of cross-cultural competency. Based on the results of our consideration of Islamic legal texts and theoretical studies, we suggest that more work is needed on formulating assimilation and inclusion within this intercultural competence. Finally, the article lists proposals concerning this important subject.
Keywords: intercultural competence; multiculturalism; values; Islamic religious law